Lack of harmonization in high fluorescent cell automated counts with body fluids mode in ascitic, pleural, synovial, and cerebrospinal fluids. (13th February 2019) - Buoro, Sabrina; Seghezzi, Michela; Dominoni, Paola; Moioli, Valentina; Manenti, Barbara; Previtali, Giulia; Ottomano, Cosimo; Lippi, Giuseppe
Abstract: Introduction: Cellular analysis in body fluids (BFs) provides important diagnostic information in various pathological settings. This study was hence aimed at comparing automated cell count obtained with Mindray BC‐6800 (BC‐BF) vs Sysmex XN‐series (XN‐BF) and evaluating other quantitative and qualitative information provided by these analyzers in ascitic (AF), pleural (PF), synovial (SF), and cerebrospinal (CSF) fluids. Methods: Three hundred and fifty‐one samples (99 AFs, 45 PFs, 75 SFs, and 132 CSFs) were analyzed in parallel with BC‐BF, XN‐BF, and optical microscopy (OM). The study also included the assessment of diagnostic agreement among BC‐BF, XN‐BF, and OM. Results: The comparison of BC‐BF vs XN‐BF yielded slopes of Passing and Bablok regression always comprised between 0.9 and 1.0 except for EO‐BF and HF‐BF, whilst the intercepts ranged from −0.4 for MN‐BF and 12.0 for PMN‐BF. The bias was comprised between −103.3% and 67.1% for HF‐BF and EO‐BF, respectively. A significant bias was found for TC‐BF, WBC‐BF, HF‐BF (negative bias) and for PMN‐BF and EO‐BF (positive bias). The agreement (Cohen's kappa) between XN‐BF and BC‐BF was always ≥0.7, ranging between 0.87 in CSFs and 0.94 in AFs, and that with OM was similar (ie, 0.85 and 0.96). Conclusion: The cytometric analysis of BF samples using BC‐BF and XN‐BF is clinically favorable when appropriately combined with OM. Quantitative and qualitative parameters displayed optimal agreement, whilst instrument‐specific cut‐offs should be defined and implemented for HF‐BF and EO‐BF. Further efforts should be made for achieving better harmonization in cytometric analysis of BF samples.